Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia.Part I. Genera Chaetosciara Frey, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Keilbachia Mohrig, Lobosciara Steffan, Phytosciara Frey and Scatopsciara Edwards - Mohrig, Werner; Kauschke, Ellen; Broadley, Adam (Zootaxa, 2017)
This study is the first of a taxonomic series on the Sciaridae of Australia, starting with the sciarid fauna of Queensland. Twelve species described herein are new to science. These are Chaetosciara recondita Mohrig & Kauschke sp. n., Cratyna adulterina Mohrig & Kauschke sp. n., Cr. flagriola Mohrig & Kauschke sp. n., Cr. flavothoracica Mohrig & Kauschke sp. n., Cr. livida Mohrig & Kauschke sp. n., Cr. longipeda Mohrig & Kauschke sp. n., Cr. pullata Mohrig & Kauschke sp. n., Epidapus excelsus Mohrig & Kauschke sp. n., Keilbachia adstrictatula Mohrig & Kauschke sp. n., Scatopsciara brevicolla Mohrig & Kauschke sp. n., Sc. dubiosa Mohrig & Kauschke sp. n., and Sc. validovenosa Mohrig & Kauschke sp. n. Seven species are new reports for Australia. These are Cratyna flagria Mohrig, Cr. vera Mohrig, Phytosciara bella Mohrig, Ph. conturbata Mohrig, Ph. pseudoornata Mohrig and Corynoptera gladiota Mohrig, previously described from Papua New Guinea, and Lobosciara trilobata Vilkamaa & Hippa, described from Sulawesi.